2015
DOI: 10.5935/0004-2749.20150081
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic wound dehiscence after corneal keratoplasty

Abstract: Purpose: To assess patient characteristics, risk factors, outcomes, and the treatment of wound dehiscence (WD) in patients after corneal keratoplasty. Methods: Retrospective chart review of 11 eyes of 11 patients with corneal grafts who underwent repair of WD from January 1, 2004 to December 31, 2012 at Hospital Oftalmologico de Brasilia. Results: Eight (72.7%) patients were men and three were women. Six (54.5%) patients had deep anterior lamellar keratoplasty (DALK) and 5 had penetrating keratoplasty. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…An experimental investigation disclosed that the junction after corneal transplantation could never return to normal intensity. In addition, increasing evidence indicated that WD was a lasting risk in all patients undergoing keratoplasty, regardless of their age, the type of operation, indication for surgery, and time to dehiscence after corneal transplantation [ 15 ]. Therefore, such patients should pay attention to take long-term protective measures such as wearing safety glasses.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental investigation disclosed that the junction after corneal transplantation could never return to normal intensity. In addition, increasing evidence indicated that WD was a lasting risk in all patients undergoing keratoplasty, regardless of their age, the type of operation, indication for surgery, and time to dehiscence after corneal transplantation [ 15 ]. Therefore, such patients should pay attention to take long-term protective measures such as wearing safety glasses.…”
Section: Discussionmentioning
confidence: 99%
“…Globe rupture in eyes treated by corneal transplantation is a serious-clinical condition that may result in loss of vision. 1,2 Several studies have reported the clinical outcome, incidence and causes of trauma in cases of globe rupture after keratoplasty. [1][2][3][4][5][6][7][8][9][10] The incidence of traumatic globe dehiscence after penetrating keratoplasty (PKP) has been reported to be 0.23-5.8%.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Several studies have reported the clinical outcome, incidence and causes of trauma in cases of globe rupture after keratoplasty. [1][2][3][4][5][6][7][8][9][10] The incidence of traumatic globe dehiscence after penetrating keratoplasty (PKP) has been reported to be 0.23-5.8%. 3,5,[8][9][10] Keratoplasty exposes patients to a higher risk of globe rupture because the surgical wound may never regain the strength and stability of an intact cornea.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations